Analisis Pengelolaan Keuangan Daerah Di Kota Jayapura Pada Era Otonomi Khusus - Halomoan Hutajulu (Jurnal Ekonomi dan Bisnis, 2014)
The implementation of the Special Autonomy (Special Autonomy) in accordance with Law No. 21, 2001, is an effort to accelerate the development and distribution of areas in the city of Jayapura. Implementation OTSUS is the equation of regional autonomy of local governments and financial management. The purpose of this study to analyze the financial management aspects of the area in terms of effectiveness, and budget planning after special autonomy, and justice analyze budget allocations. Quantitative analysis of the research approach consisting of a horizontal analysis, vertical analysis, and conversion analysis. The results showed that the effectiveness of the financial management of Jayapura city district in the Special Autonomy less effective, analysis of revenue and revenue growth ratio high of 37.33 percent and lowest 6.07. Ratio highest balanced fund 49.55 percent in 2006. Highest expenditure ratio reached 47.13 percent. The results showed a tendency analyst highest revenue growth in 2009 of Rp45.103 Billion, followed by the highest propensity balanced fund Rp567.980 Billion in 2009, the trend of the highest expenditures Rp451.190 Billion in 2009, the highest real development expenditure Rp208.063 Billion in 2008, the highest absorbed construction Rp147.418 Billion in 2006. Financial planning area is under estimated to PAD, whereas the conversion of the budget shows the budget surplus in 2002 and 2007.